STUPID WHITE MEN: ...and Other sorry excuses for the State of the Nation! - Moore, Michael, 1954-, author 581391 (New York: Regan Books, 2001)
Social commentary from famously glib liberal Michael Moore, author of ROGER & ME, features his unique takes on politicians, businessmen, and other power players who have put us into the mess we're in. Targets here include George W. Bush and the people around him, Bill Clinton, the Supreme Court, the media, and, ultimately, mediocrity.